2012
DOI: 10.1590/s1984-29612012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of sheep, municipality of Lajes, Rio Grande do Norte, Brazil

Abstract: This study investigated the gastrointestinal parasitism by helminths and protozoa in sheep (Ovis aries) Santa Inês breed, municipality of Lajes, Rio Grande do Norte. Monthly, from April 2005 to August 2007, stool samples were collected from two tracer lambs in the first day of the experiment and performed a necropsy of these animals in 44th day. A total of 64 lambs were sampled, but only 62 lambs were slaughtered. The fecal samples were examined by sedimentation in water. The contents of the abomasum, small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
8
0
4
Order By: Relevance
“…Segundo Vercruysse (1982), Chhabra e Pandey (1991) e Tembue et al (2009), E. intricata acomete, embora em percentuais baixos e suficientes para não desencadear quadro patogênico, não apenas os ovinos, mas também caprinos. Nestes animais, observa-se que E. intricata é um coccídeo que apesar de presente, não representa um grave problema para estes organismos, pois os mesmos podem não ser os responsáveis pelas fortes diarreias sanguinolentas e perdas nos rebanhos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Segundo Vercruysse (1982), Chhabra e Pandey (1991) e Tembue et al (2009), E. intricata acomete, embora em percentuais baixos e suficientes para não desencadear quadro patogênico, não apenas os ovinos, mas também caprinos. Nestes animais, observa-se que E. intricata é um coccídeo que apesar de presente, não representa um grave problema para estes organismos, pois os mesmos podem não ser os responsáveis pelas fortes diarreias sanguinolentas e perdas nos rebanhos.…”
Section: Resultsunclassified
“…desencadeia em ovinos infecções subclínicas que limitam a produtividade dos rebanhos. Neste estado, oocistos deste protozoário foram registrados para região central, Lajes, por Souza et al (2012) e para região oeste, por Ahid et al (2008)…”
Section: Introductionunclassified
“…Fecal examination of sheep revealed that the overall prevalence rate of GIT parasites was 92.6%. In comparison, coprological surveys with similar design conducted in Turkey [21], Spain [22], Bulgaria [23], Republic of Moldova [24], Kenya [25], Brazil [26], Ethiopia [20], Serbia [27], Papua New Guinea [28], India [29], Serbia [30], Nigeria [31], Colombia [17], and Pakistan [32] the prevalence of GIT parasites was 100%, 100%, 98.5%, 94%, 80%, 76.6%, 75.3%, 74.5%, 72%, 68.7%, 64.1% 63.2%, 63.0%, and 53.3%, respectively. In Romania, the study conducted by Indre et al [33] in several flocks from the western part of the country highlighted an overall GIT parasites prevalence value of 75%, but in this study the investigations were focused only on the survey of the occurrence of GIT nematodes and trematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Com relação à sanidade, entre os vários problemas enfrentados pelos produtores de caprinos e ovinos, as parasitoses gastrintestinais, cujos agentes etiológicos são espécies de nematódeos pertencentes à Superfamília Trichostrongyloidea, continua sendo o mais importante do ponto de vista sanitário dos rebanhos, e as manifestações deste parasitismo dependem de quais espécies de nematódeos estão presentes, a intensidade da infecção, a categoria e o estado geral do hospedeiro (Vieira, 2008). Oesophagostomum sp, Cooperia spp, Haemonchus sp, Trichostrongylus spp e Bunostomum sp são os membros da superfamília Trichostrongyloidea encontradas com mais frequência, sendo Haemonchus contortus o nematódeo mais abundante entre os causadores de parasitoses gastrintestinais de caprinos e ovinos, embora outras espécies possam ser mais prevalentes em alguns casos (Souza et al, 2012).…”
Section: Introductionunclassified